2022
DOI: 10.4103/jfmpc.jfmpc_975_22
|View full text |Cite
|
Sign up to set email alerts
|

Post maxillectomy rehabilitation and amelioration of quality of life of post-COVID rhinocerebral mucormycosis patients using obturator: A case series

Abstract: A BSTRACT Mucormycosis, a rare fungal infection seen in diabetes, is now very frequent owing to the deadly triad of COVID-19 infection, diabetes, and rampant use of corticosteroids. Early diagnosis and treatment can reduce the mortality and morbidity of this lethal fungal infection. Treatment principles may include antifungal agents along with surgical debridement or resection. The surgically removed palate can have a devastating effect on the appearance and speech of the patient. Obtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…27 Recent case reports have documented 10 patients with history of post covid mucormycosis (PCM) who were efficiently rehabilitated with obturators (Table 1, Table 2). [19][20][21][22][23]28,29 Diabetes mellitus was the most significant associated risk factor in 27 patients followed by Acute Myeloid Leukemia based on data reported here and earlier by Santos et al Rhizopus oryzae has been reported to be the most common causative organism as high glucose levels, insulin resistance and ketoacidosis encourage its growth. 30 Amphotericin B remained the first-choice drug followed by Posaconazole.…”
Section: Data Acquisition and Observationsmentioning
confidence: 76%
See 1 more Smart Citation
“…27 Recent case reports have documented 10 patients with history of post covid mucormycosis (PCM) who were efficiently rehabilitated with obturators (Table 1, Table 2). [19][20][21][22][23]28,29 Diabetes mellitus was the most significant associated risk factor in 27 patients followed by Acute Myeloid Leukemia based on data reported here and earlier by Santos et al Rhizopus oryzae has been reported to be the most common causative organism as high glucose levels, insulin resistance and ketoacidosis encourage its growth. 30 Amphotericin B remained the first-choice drug followed by Posaconazole.…”
Section: Data Acquisition and Observationsmentioning
confidence: 76%
“…5 I. E. Ali, et al reported prosthodontic rehabilitation of post mucormycosis defects from 30 case reports published between 2010 to 2021. 24 18 more patients on PubMed [17][18][19][20][21][22][23] and 9 on google scholar [Table 2] were reported with history of mucormycosis followed by fabrication of palatal obturator from 2020 to May 2023. Mean age and gender wise distribution of patients who were rehabilitated after surgical management of mucormycosis has been depicted in Figure 1.…”
Section: Data Acquisition and Observationsmentioning
confidence: 99%